Negotiating Individual Employment Relations, Evidence from four Dutch Organizations - Jan de Leede; Rien Huiskamp; Peter Oeij; Aukje Nauta; Anneke Goudswaard; Tobias Kwakkelstein (Revue Interventions Économiques)
Our purpose is to assess the actual experiences of companies in the context of individualised employment relationships. We have three questions: (1) what issues of the employment relationship can be individually negotiated in organizations? (scope); (2) what issues of the employment relationship are individually negotiated in organizations? (actual use); (3) what are the advantages and disadvantages of negotiations according to employees and managers?; We conducted four case studies in Dutch companies in different sectors (telecom, insurance, manufacturing and consultancy). The data were collected in a total of 69 semi-structured interviews with line managers, HR managers and shop floor employees. We focused on five topics of the employment relation: contract, working hours, wages, development and performance. We found that the scope for negotiation differs according to topic: there is considerable scope with regard to working hours, development and contract and little scope with regard to wages and performance goals. However, employees and supervisors use the scope for negotiating only for working hours and to a lesser extent development. On other topics negotiations hardly take place (e.g. contract) or only under specific conditions (e.g. performance goals in non-routine processes). Furthermore, we found that employees and managers perceive both advantages and disadvantages of negotiations. Considering the (dis) advantages our conclusion is that there must be an optimum in the scope and use of negotiating the employment relationship in order to serve conditions as fairness, fit, cost effectiveness and extra-role behaviour.Our paper provides empirical data on how individualised employment relations take place in practice. It offers insight in different companies on the scope for, the actual use of and the effects of individual negotiations on different aspects of the employment relationship.